Un paradis sans corps ? Festins célestes et ivresses spirituelles dans l’Angleterre anglo-saxonne - Alban Gautier (Revue des Langues Romanes)
In the religious literature of Anglo-Saxon England, allusions to the destiny and appearance of the blessed dead in the other world generally include, as expected in a Christian context of belief in the resurrection of the flesh, mentions of their bodies, and particularly of their food habits. The repertoire of this spiritual literature normally includes representations of spiritual ebriety, the word of God as food and paradise as a place for feasting. However, those images are given in many nuances, between prose and poetry, Latin and Old English texts. Whereas Latin prose tends to evoke bodies and food without reluctance, vernacular poetry appears much more cautious towards such representations.